Methylation-sensitive Regulation of TMS1/ASC by the Ets Factor, GA-binding Protein-α - Lucas, Mary E.; Crider, Krista S.; Powell, Doris R.; Kapoor-Vazirani, Priya; Vertino, Paula M. (The Journal of biological chemistry, 2009)
Epigenetic silencing involving the aberrant DNA methylation of promoter-associated CpG islands is one mechanism leading to the inactivation of tumor suppressor genes in human cancers. However, the molecular mechanisms underlying this event remains poorly understood. TMS1/ASC is a novel proapoptotic signaling factor that is subject to epigenetic silencing in human breast and other cancers. The TMS1 promoter is embedded within a CpG island that is unmethylated in normal cells and is spanned by three DNase I-hypersensitive sites (HS). Silencing of TMS1 in cancer cells is accompanied by local alterations in histone modification, remodeling of the HS, and hypermethylation of DNA. In this study, we probed the functional significance of the CpG island-specific HS. We identified a methylation-sensitive complex that bound a 55-bp intronic element corresponding to HS2. Affinity chromatography and mass spectrometry identified a component of this complex to be the GA-binding protein (GABP) α. Supershift analysis indicated that the GABPα binding partner, GABPβ1, was also present in the complex. The HS2 element conferred a 3-fold enhancement in TMS1 promoter activity, which was dependent on both intact tandem ets binding sites and the presence of GABPα/β1 in trans. GABPα was selectively enriched at HS2 in human cells, and its occupancy was inversely correlated with CpG island methylation. Down-regulation of GABPα led to a concomitant decrease in TMS1 expression. These data indicate that the intronic HS2 element acts in cis to maintain transcriptional competency at the TMS1 locus and that this activity is mediated by the ets transcription factor, GABPα.